Reduction of Tendon Adhesions following Administration of Adaprev, a Hypertonic Solution of Mannose-6-Phosphate: Mechanism of Action Studies - Wong, Jason K. F. (PLoS One, 2014)
Repaired tendons may be complicated by progressive fibrosis, causing adhesion formation or tendon softening leading to tendon rupture and subsequent reduced range of motion. There are few therapies available which improve the gliding of damaged tendons in the hand. We investigate the role of Mannose 6-phosphate (M6P) in a 600 mM hypertonic solution (Adaprev) on tendon adhesion formation in vivo using a mouse model of severed tendon in conjunction with analysis of collagen synthesis, cellular proliferation and receptors involved in TGF beta signalling. Cytotoxicity was assessed by measuring tissue residency, mechanical strength and cell viability of tendons after treatment with Adaprev. To elicit potential modes of action, in vitro and ex vivo studies were performed investigating phosphorylation of p38, cell migration and proliferation. Adaprev treatment significantly (p<0.05) reduced the development of adhesions and improved collagen organisation without reducing overall collagen synthesis following tendon injury in vivo. The bioavailability of Adaprev saw a 40% reduction at the site of administration over 45 minutes and tendon fibroblasts tolerated up to 120 minutes of exposure without significant loss of cell viability or tensile strength. These favourable effects were independent of CI-MPR and TGF-β signalling and possibly highlight a novel mechanism of action related to cellular stress demonstrated by phosphorylation of p38. The effect of treatment reduced tendon fibroblast migration and transiently halted tendon fibroblast proliferation in vitro and ex vivo. Our studies demonstrate that the primary mode of action for Adaprev is potentially via a physical, non-chemical, hyperosmotic effect.